-16+3n=8n-3(n-4)

Simple and best practice solution for -16+3n=8n-3(n-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16+3n=8n-3(n-4) equation:


Simplifying
-16 + 3n = 8n + -3(n + -4)

Reorder the terms:
-16 + 3n = 8n + -3(-4 + n)
-16 + 3n = 8n + (-4 * -3 + n * -3)
-16 + 3n = 8n + (12 + -3n)

Reorder the terms:
-16 + 3n = 12 + 8n + -3n

Combine like terms: 8n + -3n = 5n
-16 + 3n = 12 + 5n

Solving
-16 + 3n = 12 + 5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5n' to each side of the equation.
-16 + 3n + -5n = 12 + 5n + -5n

Combine like terms: 3n + -5n = -2n
-16 + -2n = 12 + 5n + -5n

Combine like terms: 5n + -5n = 0
-16 + -2n = 12 + 0
-16 + -2n = 12

Add '16' to each side of the equation.
-16 + 16 + -2n = 12 + 16

Combine like terms: -16 + 16 = 0
0 + -2n = 12 + 16
-2n = 12 + 16

Combine like terms: 12 + 16 = 28
-2n = 28

Divide each side by '-2'.
n = -14

Simplifying
n = -14

See similar equations:

| X=1/2(3X-2+2) | | 20y^2=21y-4 | | 3(x+8)-8=3x-19 | | cos^2(4x)+cos(4x)=0 | | X=1/2(3X-2) | | m^2-20=8m | | 7x^2+6x=5 | | X=2(3X-2) | | -6(x-10)=-12 | | 5x^6y^3= | | 25X=2(3X-2) | | -3x-5=4x-6 | | 685=85-2x | | a=bh/2 | | (8+2x)5=-28x+2 | | -4(x+2)=-8 | | 1.5(2e-30)+2e=135 | | 3.7j+1.9=16.7 | | (16a^5b^-5)^-4/(2a^6b^-2)^-4 | | 6-3=x | | 9/103 | | y(8x-9y)dx+2x(x-3y)dy=0 | | 3xy=20 | | x^2+6=-9x | | x(-3/11-5/9x)=0 | | -4y-8=4(2y+3) | | 24x^3+18x^2-6x= | | 2.1x-8.6=6.1 | | 3(x-6)=117*13 | | -2-(-85)= | | 2x^2+7x-18=0 | | -10=(n+1)2 |

Equations solver categories